Altered offspring neurodevelopment in an L-NAME-induced preeclampsia rat model - Nakamura, Noriyuki; Ushida, Takafumi; Onoda, Atsuto; Ueda, Kazuto; Miura, Ryosuke; Suzuki, Toshihiko; Katsuki, Satoru; Mizutani, Hidesuke; Yoshida, Kosuke; Tano, Sho; Iitani, Yukako; Imai, Kenji; et al. (Frontiers in Pediatrics, 2023)
This is a provisional file, not the final typeset articleOffspring of the preeclampsia dam exhibited increased growth restriction at birth (52.5%), but showed postnatal catch-up growth on postnatal day 14. Several behavioral abnormalities including motor development and vestibular function in the neonatal period (negative geotaxis test: p < 0.01); motor coordination and learning skills (rotarod treadmill test: p = 0.01); and memory skills (active avoidance test: p < 0.01) in the juvenile period were observed. NeuN-positive cells in preeclampsia rats were significantly reduced in both the hippocampal dentate gyrus and cerebral cortex (p < 0.01, p < 0.01, respectively). Among the 1,270 proteins in the cerebrospinal fluid identified using liquid chromatography-tandem mass spectrometry, 32 were differentially expressed. Principal component analysis showed that most cerebrospinal fluid samples achieved clear separation between preeclampsia and control rats. Pathway analysis revealed that differentially expressed proteins were associated with endoplasmic reticulum translocation, Rab proteins, and ribosomal proteins, which are involved in various nervous system disorders including autism spectrum disorders, schizophrenia, and Alzheimer's disease.The offspring of the L-NAME-induced preeclampsia model rats exhibited key features of neurodevelopmental abnormalities on behavioral and pathological examinations similar to humans. We found altered cerebrospinal fluid protein profiling in this preeclampsia rat, and the unique protein signatures related to endoplasmic reticulum translocation, Rab proteins, and ribosomal proteins may be associated with subsequent adverse neurodevelopment in the offspring.